2018
DOI: 10.1158/1541-7786.mcr-18-0034
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Assessment of HR Deficiency, Tumor BRCA1/2 Mutations, and CCNE1 Copy Number in Ovarian Cancer: Associations with Clinical Outcome Following Platinum Monotherapy

Abstract: The current study evaluated three biomarkers [homologous recombination deficiency (HRD), tumor BRCA1/2 (tBRCA) mutations, and CCNE1 copy-number variation (CNV)] in ovarian tumors from patients enrolled on the SCOTROC4 clinical trial for associations with outcome following carboplatin monotherapy. Ovarian tumors ( = 250), with high-grade serous (HGSOC) subgroup analysis ( = 179) were classified as HRD positive (HRD score ≥42 or tBRCA mutation) and as CCNE1 amplification positive (CCNE1 CNV score >2.4). Seventy-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 23 publications
1
90
0
Order By: Relevance
“…A cohort of HGSOC was obtained from British Columbia Cancer (BCC TMA, n=308, SuppTable-1); samples of EOC from the SCOTROC4 clinical trial (n=309, SuppTable-2), chosen based on sample availability and divided equally between both study arms (23), were used as a tissue microarray (TMA). HRD score from the Myriad genomic scar assay was available for 240/309 cases on this TMA (24). Gene expression analysis, was performed on HGSOC and high grade endometrioid samples from the TCGA (n=566) (22), Australian Ovarian Cancer Study (AOCS, GSE9891; n=267) (25), Massachusetts General Hospital (MGH, GSE26712; n=185) (26) and Duke University Hospital (Duke, GSE3149; n=146) (27), which were extracted from CSIOVDB (28).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A cohort of HGSOC was obtained from British Columbia Cancer (BCC TMA, n=308, SuppTable-1); samples of EOC from the SCOTROC4 clinical trial (n=309, SuppTable-2), chosen based on sample availability and divided equally between both study arms (23), were used as a tissue microarray (TMA). HRD score from the Myriad genomic scar assay was available for 240/309 cases on this TMA (24). Gene expression analysis, was performed on HGSOC and high grade endometrioid samples from the TCGA (n=566) (22), Australian Ovarian Cancer Study (AOCS, GSE9891; n=267) (25), Massachusetts General Hospital (MGH, GSE26712; n=185) (26) and Duke University Hospital (Duke, GSE3149; n=146) (27), which were extracted from CSIOVDB (28).…”
Section: Methodsmentioning
confidence: 99%
“…SCOTROC4 was a phase III clinical trial performed to assess two different dosing schedules of single agent carboplatin in EOC (23). While the trial showed no difference between the two arms, it represents a unique cohort of single agent platinum treated ovarian cancer with well-annotated survival data and HRD scores (24). Finally, we Confidential, Hoppe et al 8/6/2020 5 use a combination of in-vitro experiments and RNA expression data from four independent ovarian cancer datasets to demonstrate that the effect of RAD51 overexpression on survival is potentially mediated through an altered immune microenvironment in RAD51-High EOC.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report found that the copy number variation of CCNE1 is a biomarker for ovarian tumours. 22 Ehedego et al found that the downregulation of CCNE1 markedly reduced the hepatitis and hepatocarcinogenesis. 29 Therefore, the investigation of the regulating network of CCNE1 in HCC is urgent.…”
Section: Zhu Et Al Showed That Ccat1mentioning
confidence: 99%
“…19,20 CCNE1, a kind of cyclins, is required for cell cycle G1/S transition. 22 In spite of a study demonstrated that the down expression of CCNE1 reduced the liver tumorigenesis significantly in a mouse model, 23 the function of CCNE1 in human HCC is poorly understood. 22 In spite of a study demonstrated that the down expression of CCNE1 reduced the liver tumorigenesis significantly in a mouse model, 23 the function of CCNE1 in human HCC is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation